Implementation of Adaptive Physical Education Learning in SLB Negeri 1 Dompu Learning Year 2022/2023 - Amal, Amal Fauqi; Zen, Mohammad Zaim; Munandar, Rizky Aris; Muhtar, Muhtar (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to examine and analyze the implementation of Adaptive Physical Education learning at the Dompu 1 State Special School (SLB) during the 2022/2023 academic year. Adaptive Physical Education is a learning method specifically designed to meet the learning needs of students with special needs at this school. This research uses a qualitative approach with the Case Study method. Data Collection Procedures carried out observations, interviews and document analysis to explore data related to the implementation of adaptive learning at SLB Negeri 1 Dompu. Based on the research results, it can be concluded that the implementation of Adaptive Physical Education Learning at SLB Negeri 1 Dompu in the 2022/2023 academic year makes a positive contribution to educational inclusion with a percentage of Student Activeness in the Learning Process of 85%. Learning strategies that are tailored to students' needs can increase student participation and learning achievement. This research can be a basis for further development in improving the quality of inclusive learning at SLB Negeri 1 Dompu and similar schools